DAMPAK LIBERALISASI PERDAGANGAN BERAS TERHADAP PERTUMBUHAN EKONOMI TAHUN 2007 - 2010 - Apriani Simatupang; Veny Anindya Puspitasari (Business Management Journal, 2017)
An export commodity is one of the macroeconomic factors that must be considered to enhance economic growth. One of the export commodities is rice. Rice is also one of the commodities that are traded in the current era of free trade. Free trade has ability to increase national income and give a trigger to the country's economic growth through international trade mechanisms. However, the phenomenon that occurs at this time, rice-as an export commodity- is at a crossroads. Rather than being a major contributor to state revenues, but it became one of the macroeconomic problems. The research looked at how the impact of rice trade liberalization on economic growth and how the influence of rice exports and imports on economic growth. Keywords : Trade liberalization, Economic growth, Rice Export, Rice Import